Pendidikan Berbasis Ruang Sosial: Studi Penghafal Al-Qur’an pada Anak Usia Dini di Dalam Keluarga - Nasrowi, Bagas Mukti; Yusuf, Moh (Borneo Journal of Islamic Education, 2022)
Abstract This study began when two families of the researcher's wife's friends had children who were still at an early age, these children aged 4 and 4.5 years. Their mother had a strong desire so that they could memorize the Qur'an. He realized the dream of being able to have a son with hafidz al-Qur'an after getting the family's approval. The practice of learning to memorize is formed in such a condition, memorizing and moroja’ah not only in a special room, such as in a house or in a prayer room, learning continues anywhere without space. in this research, the concept of spatial representation and spatial reproduction of Henri Levebvre is tried to understand technically the planning and actualization of the mothers of these children. Their mother reproduces small spaces anywhere for the sake of their children still enjoying memorizing. Within one semester, these children can memorize 1 juz of juz 30 well and fluently. Keywords: Early Childhood Education, Memorization of Al-Qur'an, Representation and Reproduction of Space